Infection and Cancer: The Case of Hepatitis B - Chan, Stephen L.; Wong, Vincent W.S.; Qin, Shukui; Chan, Henry L.Y. (Journal of clinical oncology, 2016)
Infection is a well-described cause of cancer in humans. Being one of the most common infections worldwide, hepatitis B virus (HBV) is the leading cause of hepatocellular carcinoma (HCC), particularly in Asian countries. The etiological link between HBV and HCC provides an important opportunity for health care policy makers and clinicians to intervene with HBV infection to prevent cancer development and improve the outcomes of cancer. This review aims to use HBV as an example to illustrate the potential of tackling infection-related conditions to help improve cancer outcomes. This article is divided into four parts: In the first part, an overview is given on the epidemiologic data and risk factors of HCC development in patients with chronic hepatitis B. In the second part, recent progress on the anti-HBV strategies for preventing HCC is updated. In the third part, approaches to improve the outcomes of established HBV-related HCC are covered. These methods include surveillance strategies to identify asymptomatic HCC among patients with chronic HBV infection, and use of antiviral treatment to avoid HBV reactivation during treatment for HCC and reduce the recurrence of HCC after curative treatment. Finally, the status of the development of targeted drugs specifically for HBV-related HCC is discussed in the section on future development.